Effectiveness of school-based active breaks on classroom behavior, executive functions and physical fitness in children and adolescent: a systematic review - Tomás Reyes-Amigo; Gabriel Salinas-Gallardo; Edgardo Mendoza; Camilo Ovalle-Fernández; Jessica Ibarra-Mora; Nicolás Gómez-Álvarez; Hernaldo Carrasco-Beltrán; Jacqueline Páez-Herrera; Juan Hurtado-Almonácid; Rodrigo Yañez-Sepúlveda; Rafael Zapata-Lamana; Rafael Zapata-Lamana; et al. (Frontiers in Public Health)
IntroductionThe classroom environment is ideal for promoting physical activity interventions since children spend most of their day there but often engage in sedentary behavior. Given this context, an emerging trend to promote physical activity is active breaks at school. This systematic review evaluated the effects of school-based physical activity interventions involving active breaks on children and adolescents’ classroom behavior, executive functions, and physical fitness.MethodsThis review was guided by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. A literature search was conducted using PubMed, Web of Science, Scopus, and EBSCOhost. Studies published between January 2010 and August 31, 2023, including participants aged 5 to 18, were included. Interventions involving active breaks and outcomes related to classroom behavior, executive functions, and physical fitness were considered.ResultsInitially, 145 studies were identified, with 22 duplicates excluded. After screening 123 articles by title and abstract, 86 were excluded. Subsequently, 37 articles underwent full-text screening, resulting in 22 included studies. Six studies showed positive effects on classroom behavior; five studies showed improvements in executive functions, and only two studies indicated increases in physical fitness.DiscussionThis review suggests incorporating active breaks during school hours can improve classroom behavior in children and adolescents. However, the effects of active breaks on executive functions and physical fitness are unclear. More research is needed to fully understand the benefits of implementing active break programs in the classroom.Systematic review registrationPROSPERO, CRD42023448267, available from: https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42023448267.